Traditional Settlement Patterns on The Parapat Girsang Sipangan Bolon District - Annisa Widhiyanti (International Journal of Architecture and Urbanism, 2022)
Settlement is one of the important elements including basic needs. Humans live their lives in the chosen area. Cultural and historical factors are factors that can form a settlement. Parapat is a village in the Girsang Sipangan Bolon sub-district, Simalungun Regency, North Sumatra. This village is one of the accesses to Lake Toba which is about 48 km from Pematangsiantar City. Parapat is one of the important stopover points of Jalan Raya Lintas Sumatera and has a lot of potentials, including the traditional ones in it. This research was conducted using qualitative methods through aerial map analysis to identify settlement patterns formed in Parapat. Through this research, it will be known the pattern formed in the Parapat sub-district in the context of geographical conditions as well as local social and cultural conditions